CRYSTAL STRUCTURES OF TWO PHOSPHONATE SALTS: MONOCYCLOHEXYLAMMONIUM HYDROGEN PHOSPHONATE AND MONOCYCLOHEXYLAMMONIUM PHENYL PHOSPHONATE - MODOU SARR; MOUHAMADOU BIRAME DIOP; MOUHAMADOU SEMBENE BOYE; AMINATA DIASSE-SARR; PHILIPPE GUIONNEAU (Journal of Engineering Studies and Research, 2020)
Hydrogen phosphonate anions and monocyclohexylammonium cations interacting through hydrogen bonds conduct to the formation of a salt namely monocyclohexylammonium hydrogen phosphonate. In this structure, hydrogen phosphonate anions are linked by pairs through O—H···O hydrogen bonds leading to anionic dimers. Each dimer is connected to its two neighbours through cations via N—H···O hydrogen bonds leading to infinite chains which are then connected by N—H···O hydrogen bonds giving rise to a layered structure. The phenyl phosphonates form dimers that are connected through an expended hydrogen bonding network involving the cations into a layer.